ANALISIS MUTU PELAYANAN KEFARMASIAN PASIEN RAWAT JALAN DI INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH (RSUD) MOROWALI - Nurwahida Nurwahida; Rizqi Nur Azizah; Iskandar Zulkarnain; Mirawati Mirawati (Fakultas Farmasi UMI, 2023)
The hospital pharmacy installation is a place for managing pharmaceutical preparations and clinical pharmacy services based on the quality of pharmaceutical services. The quality of pharmaceutical services is the compatibility between pharmaceutical services and applicable standards to achieve optimal health degrees and patient satisfaction. Patient satisfaction is the match between perceptions of performance and expectations. The purpose of this study was to determine the quality of outpatient pharmacy services at the pharmacy installation of Morowali Hospital. This research is a quantitative research conducted using the Cross Sectional Survey method at the Pharmacy Installation of the Morowali Regional General Hospital. Assessment of the quality of pharmaceutical services and the level of patient satisfaction was carried out by collecting questionnaires from 95 patients. The results of the research on the quality of pharmaceutical services showed that 81.1% felt good, while the results of the study for the level of patient satisfaction, as many as 97.9% stated that they were satisfied with pharmaceutical services. The results of this study illustrate that the level of satisfaction of outpatients with services at the pharmacy installation of Morowali Hospital is very good with a value of 97.9% feeling satisfied and there is a relationship between service quality and patient satisfaction level with a constant value (a) of 19.534 and the value of the quality variable coefficient service of 0.005